Anti-VEGF drug interference with VEGF quantitation in the R&D systems human quantikine VEGF ELISA kit. (20th March 2019) - Sumner, Giane; Georgaros, Camille; Rafique, Ashique; DiCioccio, Thomas; Martin, Joel; Papadopoulos, Nicholas; Daly, Thomas; Torri, Albert
Aim: To evaluate the accuracy of the Quantikine Human VEGF Immunoassay (R&D Systems) in the presence of VEGF inhibitors.Materials & Methods: Quantikine VEGF ELISA (R&D), anti-VEGF165 mAb (R&D), VEGF165 and aflibercept (Regeneron), ranibizumab and bevacizumab (Genentech).Results: Binding affinity of anti-VEGF165 mAb for VEGF was threefold weaker than aflibercept, but 33- and 40-fold stronger than ranibizumab or bevacizumab. Extended incubation of VEGF complexed with inhibitors led to VEGF dissociation from ranibizumab and bevacizumab, but not aflibercept, and subsequent binding by the immunoassay capture antibody. The immunoassay also detected VEGF:ranibizumab and VEGF:bevacizumab complexes but not VEGF:aflibercept complexes.Conclusion: The immunoassay cannot accurately quantitate VEGF in the presence of these VEGF inhibitors as they interfere with the capture and detection of free VEGF.